Monograph of the Australian Bithyniidae (Caenogastropoda: Rissooidea) - Ponder, Winston F. (Zootaxa, 2003)
The Bithyniidae is represented in Australia by a single genus-group, Gabbia Tryon, 1865. The species, including the type species of the genus, are described using shell, opercula, radular and anatomical characters. Twenty one species are recognised, 17 of them new. The genus Gabbia is redefined as incorporating a much wider diversity of shell morphology than previously envisaged with some species having smooth shells while others have strong axial or spiral sculpture or both. The following previously named species are recognised as valid: G. vertiginosa Frauenfeld (= Gabbia australis Tryon), G. iredalei Cotton, G. affinis Smith and G. smithii Tate. The 17 new species described are G. campicola n.sp., G. kendricki n.sp., G. pallidula n.sp., G. davisi n.sp., G. napierensis n.sp., G. rotunda n.sp., G. fontana n.sp., G. obesa n.sp., G. tumida n.sp., G. kessneri n.sp., G. beecheyi n.sp., G. microcosta n.sp., G. adusta n.sp., G. lutaria n.sp. G. clathrata n.sp., G. spiralis n.sp. and G. carinata n.sp. Most species live in northern Australia, with a few in the central and eastern parts but members of the family are absent from southern-most mainland Australia and Tasmania.